The Francoist repression of Galician. The dismantlement of a linguistic, cultural and national reality - Rodríguez da Torre, Matías; Baamonde Silva, Xosé Manuel (Caracol, 2016)
Galician, originally Galician-Portuguese, is a vivid language in its spoken form, which from the second half of the 19th Century to the first third of the 20th begins to restore the usual purposes of an official and standard language. Francoist repression in the year 1936 submits people to a forty-year dictatorship, imposes Spanish as the only compulsory and official language forcing Galician to become a minor language regarding its written usage and diminishing its spoken usage too. Only people in exile, mainly in America, were able to continue publishing, writing literature and denouncing the political, social and linguistic tyranny. These totalitarian decades were the key factors to develop the linguistic conflict and diglossic situation which still exists in Galiza.